The pathological features of ectopic lymphoid neogenesis in idiopathic dacryoadenitis - Guo, Jie (BMC Ophthalmol, 2016)
BACKGROUND: Lymphoid neogenesis has been reported in various diseases but not in idiopathic dacryoadenitis. The aim of this paper is to discuss the pathological features of lymphoid neogenesis in idiopathic dacryoadenitis. METHODS: 20 cases of idiopathic dacryoadenitis were collected retrospectively. Lymphoid neogenesis was graded by lymphocytic aggregates and germinal center-like structure formation. T and B cell compartmentalization, follicular dendritic cells and the expression of CXCL13 and CCL21 were analyzed. RESULTS: Grade 1 lymphoid neogenesis was observed in 10 of 20 cases (50 %), grade 2 in 18 of 20 cases (90 %) and grade 3 in 14 of 20 (70 %). The existence of T and B cell compartmentalization and follicular dendritic cells increased in parallel to the grade of lymphoid neogenesis. The expression of CXCL13 significantly increased in the higher grade of lymphoid neogenesis, but no correlation was found between CCL21 and grades of lymphoid neogenesis. CONCLUSIONS: Ectopic lymphoid neogenesis participates in the pathogenesis of idiopathic dacryoadenitis and appears as a dynamic process.